Pola Komunikasi Guru Dalam Menstimulasi Kemampuan Hots Pada Anak Usia 5 - 6 Tahun Di Paud Taman Belia Candi Semarang - Rieyani Okta Sumbawa; Muniroh Munawar; Anita Chandra Dewi Sagala (Universitas PGRI Semarang, 2022)
AbstractEarly childhood learning activities have not provided the process of children's opportunities to explore, children have not been given the opportunity to express their ideas and ideas so that children do not have direct experience in solving their own problems, children must complete an activity according to the teacher's orders, this can limit the child's learning experience . The purpose of this study was to find out how teacher communication patterns can stimulate children's HOTS abilities in PAUD Taman Belia Candi Semarang. Communication in early childhood is certainly different from communication in adults. In early childhood, in communicating children begin to be sensitive to receive various stimuli, the sensitive period for each child is also different. In order for communication to be effective, accompanying children through stimulation so that they are able to think at higher levels which are not just memorizing but also the ability to think logically, analytically, systematically, critically, and creatively, as well as the ability to work together. The levels of thinking skills are divided into low and high levels, namely remembering, understanding, applying, analyzing, evaluating, and creating. This study uses a qualitative method with the approach taken to describe the facts and data obtained from data sources taken through interviews, observation, and documentation. The results of this study are the teacher's communication patterns at PAUD Taman Belia Candi Semarang in stimulating children's HOTS abilities through STEAM-based learning, seen when teachers stimulate students in learning activities and play through effective communication patterns. Using two-way communication patterns and higher-order thinking skills in PAUD Taman Belia Candi Semarang in children aged 5-6 years, children are able to solve their own problems from very diverse problems. Keywords: HOT’s, communication, STEAMAbstrakKegiatan pembelajaran anak usia dini belum memberikan proses kesempatan anak untuk bereksplorasi, anak belum diberikan kesempatan untuk mengungkapkan ide dan gagasannya sehingga anak tidak memiliki pengalaman langsung dalam memecahkan masalahnya sendiri, anak harus menyelesaikan suatu kegiatan sesuai dengan perintah guru, hal ini dapat membatasi pengalaman belajar anak. Tujuan penelitian ini adalah untuk mengetahui bagaimana pola komunikasi guru yang dapat menstimulasi kemampuan HOTS anak di PAUD Taman Belia Candi Semarang. Komunikasai pada anak usia dini tentu berbeda dengan komunikasi pada orang dewasa. Pada anak usia dini, dalam berkomunikasi anak mulai peka untuk menerima berbagai rangsangan, masa peka pada masing-masing anak juga berbeda. Agar komunikasi menjadi efektif, mendampingi anak melalui stimulasi agar mampu berpikir tingkat tinggi yang bukan hanya sekedar menghafal tetapi lebih pada kemampuan berpikir logis, analitis, sistematis, kritis, dan kreatif, serta kemampuan bekerja sama. Tingkatan kemampuan berpikir yang dibagi menjadi tingkat rendah dan tinggi yaitu mengingat, memahami, mengaplikasikan, menganalisis, mengevaluasi, dan mencipta. Penelitian ini menggunakan metode kualitatif dengan pendekatan fakta dan data-data yang diperoleh dari sumber data yang di ambil melalui wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini adalah pola komunikasi guru di PAUD Taman Belia Candi Semarang dalam menstimulasi kemampuan HOTS anak melalui pembelajaran pembelajaran berbasis STEAM, terlihat saat guru-guru menstimulasi siswa dalam kegiatan pembelajaran dan bermain melalui pola komunikasi yang efektif. Menggunakan pola komunikasi dua arah dan kemampuan berpikir tingkat tinggi di PAUD Taman Belia Candi Semarang pada anak usia 5-6 tahun anak mampu menyelesaikan masalahnya sendiri dari masalahnya yang sangat beragam.Kata kunci: Hot’s, komunikasi, STEAM